Issues of motivation and workload affecting engagement in good teaching: The 21st Century academics' perspective. - Scott, Shelleyann; Dixon, Kathryn; Dixon, Robert; Kerr, Rosie (AARE Inc, 2007)
Can 21st Century universities afford to maintain elitist attitudes to research and reward structures which minimalise the importance of good teaching, with the underlying principle that anyone can teach and only the elite few can conduct research? This study reports on university academics’ perceptions of their work lives. In-depth interviews undertaken with thirty eight academics over five divisions revealed issues with motivation to engage with teaching, and concerns with high workloads. These academics indicated that there were mixed messages emerging from the university administration regarding the importance of teaching. The reward structures and job security were perceived to be overtly focused on the research agenda rather than good teaching. Workload was a significant issue, particularly for academics in the Business Division who were undertaking offshore teaching over and above their normal teaching load. Across the university high student numbers were impacting on academics’ capacity to deliver high quality teaching. There was no time for reflection, curriculum review, development of more professional materials, in-depth communication with students, sound feedback on assessments, and professional development of teaching strategies. There was a general positive attitude to teaching with most indicating that they wanted to be more innovative in their teaching but didn’t know how to achieve this. This paper also explores the paradox of perceptions that research brings in considerable funding to the university over teaching, whereas the opposite is the reality.